Analysis of Bike Rear Shock Breaker Faults Motor on the Under Bracket - I Gusti Bagus Eka Nitiyasa; Dinda One Mulyaningtyas; Surya Aji Ermanto; Riz Rifai O. Sause; Dynes Rizky Novianti (Jurnal Teknologi Transportasi dan Logistik, 2022)
The purpose of this study was to conduct a study related to what factors caused the occurrence of a broken motorcycle rear shock breaker at the under bracket. Shock breaker is a very important component as a damper from shock loads and shocks experienced by the vehicle under various loading conditions and the road surface traversed. This study is a follow-up to the cases the team found in the field. The next research step, begins with a literature review, determining the test flow based on the hypothesis, conducting tests on the samples obtained, analyzing the test data and finally making research conclusions. This research method was carried out sequentially from beginning to end. This can have an impact on consumer confidence in motorcycle related products, 27% for FOB incoterms, 23% for delivery services using CIF incoterms, 12% for EXW incoterms and 8% for DPU incoterms.